Elemental mapping of Neuromelanin organelles of human Substantia Nigra: correlative ultrastructural and chemical analysis by analytical transmission electron microscopy and nano‐secondary ion mass spectrometry. Issue 2 (2nd June 2016) - Biesemeier, Antje; Eibl, Oliver; Eswara, Santhana; Audinot, Jean‐Nicolas; Wirtz, Tom; Pezzoli, Gianni; Zucca, Fabio A.; Zecca, Luigi; Schraermeyer, Ulrich
Abstract: Neuromelanin (NM) is a compound which highly accumulates mainly in catecholamine neurons of the substantia nigra (SN), and is contained in organelles (NM‐containing organelles) with lipid bodies and proteins. These neurons selectively degenerate in Parkinson's disease and NM can play either a protective or toxic role. NM‐containing organelles of SN were investigated by Analytical Electron Microscopy (AEM) and Nano‐Secondary Ion Mass Spectrometry (NanoSIMS) within human tissue sections with respect to ultrastructure and elemental composition. Within the NM‐containing organelle, the single NM granules and lipid bodies had sizes of about 200–600 nm. Energy‐Dispersive X‐ray microanalysis spectra of the NM granules and lipid bodies were acquired with 100 nm beam diameter in AEM, NanoSIMS yielded elemental maps with a lateral resolution of about 150 nm. AEM yielded the quantitative elemental composition of NM granules and bound metals, e.g., iron with a mole fraction of about 0.15 atomic percent. Chemical analyses by AEM and NanoSIMS were consistent at the subcellular level so that nanoSIMS measurements have been quantitated. In NM granules of SN from healthy subjects, a significant amount of S, Fe, and Cu was found. In lipid bodies an amount of P consistent with the presence of phospholipids was measured. The improved detection limits of nanoSIMS offer new possibilities for chemical mapping, high‐sensitivity trace element detection, and reduced acquisition times. Variations between individual NM granules can now be investigated effectively and quantitatively by NanoSIMS mapping Cu and Fe. This should yield new insight into the changes in chemical composition of NM pigments during healthy aging and disease. Neuromelanin‐containing organelles of dopamine neurons in normal human substantia nigra were investigated by analytical electron mircoscopy and secondary ion mass spectroscopy (NanoSIMS) yielding the ultrastructure and elemental composition. In neuromelanin granules a significant amount of S, Fe and Cu was found. In lipid bodies an amount of P consistent with the presence of phospholipids was measured. The improved sensitivity of NanoSIMS shows differences in chemical composition between individual neuromelanin granules and allows to study chemical changes of neuromelanin organelles during aging and disease. Abstract : Neuromelanin‐containing organelles of dopamine neurons in normal human substantia nigra were investigated by analytical electron mircoscopy and secondary ion mass spectroscopy (NanoSIMS) yielding the ultrastructure and elemental composition. In neuromelanin granules a significant amount of S, Fe and Cu was found. In lipid bodies an amount of P consistent with the presence of phospholipids was measured. The improved sensitivity of NanoSIMS shows differences in chemical composition between individual neuromelanin granules and allows to study chemical changes of neuromelanin organelles during aging and disease.